Advances in Modelling and Control of Wind and Hydrogenerators - Ebrahimi, Amir; Ebrahimi, Amir (2020)
Rapid deployment of wind and solar energy generation is going to result in a series of new problems with regards to the reliability of our electrical grid in terms of outages, cost, and life-time, forcing us to promptly deal with the challenging restructuring of our energy systems. Increased penetration of fluctuating renewable energy resources is a challenge for the electrical grid. Proposing solutions to deal with this problem also impacts the functionality of large generators. The power electronic generator interactions, multi-domain modelling, and reliable monitoring systems are examples of new challenges in this field. This book presents some new modelling methods and technologies for renewable energy generators including wind, ocean, and hydropower systems.
Knowledge Unlatched
English
Keywords: Fluid mechanics; Science; Mechanics; Hydrodynamics